2012
DOI: 10.1371/journal.pone.0044327
|View full text |Cite
|
Sign up to set email alerts
|

Conflict of Interest in Spine Research Reporting

Abstract: BackgroundMedical studies are more likely to report favorable findings when a conflict of interest is declared. We aim to quantify and determine the effect of author disclosure of conflict of interest on scientific reporting.MethodsAbstracts from an international spine research meeting (North American Spine Society 2010) were selected that specifically evaluated a device, biologic, or proprietary procedure. They were then made anonymous to reviewers. An item of interest was established in each of the abstracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
10
1
Order By: Relevance
“…While previous studies have shown that the presence of conflict of interest tends to affect the significance or direction of results reported, in our study, no such associations were found ( 4 ). The primary reason that we were unable to report on this is due to the small number of papers that were determined to have a conflict of interest.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…While previous studies have shown that the presence of conflict of interest tends to affect the significance or direction of results reported, in our study, no such associations were found ( 4 ). The primary reason that we were unable to report on this is due to the small number of papers that were determined to have a conflict of interest.…”
Section: Discussioncontrasting
confidence: 89%
“…Companies that produce drugs or medical devices are often susceptible to conflicts of interest, as their funding can impact reporting of the results, and general design and outcomes of medical research trials ( 3 ). This is illustrated by the finding that industry-sponsored studies more frequently express positive results towards that industry or product, than do studies that have alternative sources of funding ( 4 , 5 ). For these reasons, transparency in reporting conflict of interest in medical journals has been a very important topic of discussion over the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the spine literature have reported similar findings of a high rate of favorable outcomes. 3 , 30 Given the 11% difference in positive outcomes, it is possible that the present study was underpowered to detect a difference. Similarly, publication bias toward positive outcomes may have suppressed the number of available studies with unfavorable outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…Contributing authors seem to have less COI than the reviewers analyzed in the current study. Regarding NASS meetings, a COI was reported for 10% of all presentations in 1985, increasing to 32% in 2002 [ 11 ]. In the 2006 SRS Annual Meeting, there were 27.9% of authors declaring COI [ 12 ].…”
Section: Discussionmentioning
confidence: 99%